New Mnemosynini taxa (Hemiptera, Fulgoromorpha: Cixiidae) from the Palaeogene of France with notes on their early association with host plants - Szwedo, Jacek; Bourgoin, Thierry; Lefebvre, Fabrice (Zootaxa, 2006)
Three new genera: Stalisyne gen. nov. comprising S. lutetiorum sp. nov. and S. veromanduiorum sp. nov., Mnaomaia gen. nov. for M. bellovaciorum sp. nov., both from the Lowermost Eocene (Sparnacian) amber of Oise, (Northern France) and Mnasthaia gen. nov. for M. arverniorum sp. nov. from the Palaeocene strata of Menat (Auvergne) are described. Characters of extant and fossil Mnemosynini are discussed also. Remarks on co-evolutionary processes of Mnemosynini, as well as Cixiidae and the host plants are presented. Eco-evolutionary processes affecting Mnemosynini and other Cixiidae lineages are presented.